THE EFFECT OF HEALTHCARE PROVIDERS’ SERVQUAL DIMENSIONS ON PATIENT LOYALTY AT ARJASA COMMUNITY HEALTH CENTER - Lusiawati, Siti; Silalahi, Amin; Saputra, Harmawan Teguh (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Community health centers (puskesmas) play a vital role in delivering primary healthcare services, where the quality of medical personnel services is a key determinant of patient loyalty. Despite an improvement in the Community Satisfaction Index (IKM) at Arjasa Community Health Center from 78.5% in 2023 to 81.2% in 2024, patient loyalty has not yet reached an optimal level. This study applies the SERVQUAL framework to examine how service quality influences patient loyalty in a primary healthcare context. Methods: This study employed an associative quantitative approach with a correlational survey design. Data were collected from 100 patients at Arjasa Community Health Center using a questionnaire consisting of 15 SERVQUAL items and 6 patient loyalty items. Data analysis was conducted in SPSS, including validity and reliability tests and simple linear regression.Results: The findings indicate that medical personnel’s SERVQUAL has a significant and positive effect on patient loyalty. The regression analysis yielded a correlation coefficient (R) of 0.637 and a coefficient of determination (R²) of 0.405, indicating that 40.5% of the variation in patient loyalty is explained by service quality. The F-test confirmed that the regression model is statistically significant (F = 66.842; p < 0.001). The t-test results showed that SERVQUAL exerts a significant partial effect on patient loyalty (t = 8.176; p < 0.001), with responsiveness and empathy emerging as the most influential dimensions in shaping patient loyalty at the community health center.Conclusion and suggestion: This study concludes that service quality among medical personnel, measured using the SERVQUAL model, significantly predicts patient loyalty in primary healthcare settings. Responsiveness and empathy play dominant roles in strengthening long-term patient relationships. Accordingly, Arjasa Community Health Center should prioritize the development of interpersonal competencies through communication training, reinforcement of empathetic service attitudes, and improved service time management. Future studies should include variables and samples to enhance generalizability. Keywords: Community Health Center, Medical Personnel; Patient Loyalty; SERVQUAL